THE INFLUENCE OF THE DUTCH EAST INDIES GOVERNMENT’S ETHNIC POLITICS ON DISCRIMINATION AGAINST THE CHINESE ETHNIC GROUP IN BATAVIA (1946–1950) - Fadrin, Zaky Rizqy Zaidaan; Muhammad Nugraha, Fajar Muhammad (UI Scholars Hub, 2025)
This study explains how discrimination was experienced by ethnic Chinese in Batavia in the early post-independence period in 1946–1950, with an emphasis on the influence of ethnic politics practiced by the Dutch East Indies colonial government. The purpose of this study is to analyze the pattern of discrimination against ethnic Chinese influenced by the legacy of colonial racial segregation. The method used is qualitative historical descriptive. The main sources of this study come from letters of complaint from the Chinese community in 1946–1949 in the National Archives of the Republic of Indonesia (ANRI) and newspaper articles from 1950 from De Bredasche Courant, De Telegraaf, Indische Courant, and Het Nieuwsblad voor Sumatra. The results of the study show that discrimination against ethnic Chinese cannot be separated from the socio-political construction of the colonial era, and this legacy continues to influence inter-ethnic relations in the early days of the Republic of Indonesia.